Symbiotic Intelligence (Springer Nature, 2025)
This open access book is a compilation of selected papers from The 6th International Conference on Computational Design and Robotic Fabrication (CDRF 2024). The work focuses on novel techniques for computational design and robotic fabrication. The contents make valuable contributions to academic researchers, designers, and engineers in the industry. Also, readers will encounter new ideas about understanding symbiotic intelligence in architecture.